Improve Performance in Software Defined Network Controller’s (HPE VAN) Using Computer Network Functionality Equipment - محايري, محمد; حمدان, رؤوف; حرفوش, نزيه (Latakia University Journal -Engineering Sciences Series, 2021)
Computer networks today rely on a wide range of Middleboxes specialized to improve network security and performance by providing services such as firewall and network address translation (NAT) as well as load balancing. In their management, these networks resort to Software Defined Networks (SDN), which can provide a central programmable environment that is used to direct traffic by achieving the required service chain so that the middleboxes are implemented as programs in virtual machines in Software Defined Networks (SDN) [[1]]. However, even if the SDN controller is able to determine the best path for a specific middlebox (network function equipment), lack of prior knowledge of the policy of this equipment may lead to traffic jams, which leads to a significant decrease in network performance in general. By considering the characteristics of the used equipment and the characteristics of software defined networks (SDN), a lightweight and cost-effective routing method that is aware of the network functionality equipment policy will be designed to address this challenge. That is, a middle box is added to the SDN structure to help this equipment give "hints" to guide the REST API in order to make better routing decisions.